THE EFFECT OF THE INTERVAL OF APPLICATION OF VENTILATION SYSTEM ON DRYING DURATION OF SEEDLESS GRAPE VARIETIES BY SHIELD DRYING - Sh. Y. Dexkonova; O. N. Sulaymonov; G. A. Ortikova (Web of Journals Publishing, 2024)
This article proves that the duration of the process is reduced by 40-45% by using the ventilation system in the drying of seedless Kishmish chyorny and Sogdiana grapes in the conditions of Andijan region. When drying seedless varieties of grapes in the shade method, it was determined that the frequency of operation of the ventilation system at an interval of 180-240 minutes gives the highest effect.